Internet Reporting Timeliness: Influential Factors in Indonesian Listed Companies: Kecepatan Pelaporan Keuangan di Internet: Faktor-Faktor Penentu pada Perusahaan Terdaftar di Indonesia - Hadyan Caesar Ahmargatu; Sigit Hermawan (Academia Open, 2023)
This research investigates the factors influencing the timeliness of financial reporting on the internet by examining a sample of 70 annual reports from 12 companies listed in the Indonesian Stock Exchange (IDX) over a period of 5 years. The study considers various company characteristics, such as profit margin, return on assets, return on equity, earnings per share, liquidity, and debt to assets ratio, and analyzes their impact on reporting timeliness. The results indicate that these company characteristics significantly affect the timeliness of reporting on the internet, except for the variables of Return On Investment and Debt To Equity Ratio. Furthermore, the study examines the influence of corporate governance, specifically the board of directors and the board of commissioners, on reporting timeliness. The findings reveal that the board of directors has a significant effect on timeliness, whereas the board of commissioners does not. However, firm size is not found to have an impact on reporting timeliness. These results contribute to the understanding of factors shaping financial reporting practices in the internet era and have implications for businesses, investors, and regulatory bodies in enhancing the efficiency and transparency of financial information dissemination. Highlights: The study investigates factors influencing the timeliness of financial reporting on the internet. Company characteristics significantly affect reporting timeliness, except for Return On Investment and Debt To Equity Ratio. The board of directors has a significant impact on reporting timeliness, while the board of commissioners does not. Keywords: Internet reporting, Financial reporting, Timeliness, Indonesian listed companies, Factors